Preparation method of perovskite fluorescent quantum dot continuous long fiber
By adopting lead ion rivet strategy and ion coordination technology in perovskite quantum dot materials and combining wet spinning, the stability and safety of perovskite quantum dots in complex environments is solved, and efficient fluorescence is achieved Fiber preparation, suitable for flexible electronic display.
Patent Information
- Application Number
- CN202311512073.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-14
- Publication Date
- 2024-12-13
AI Technical Summary
Perovskite quantum dot materials are insufficient in complex environmental conditions, and are prone to lose structural integrity and optical properties in water and polar solvents, resulting in limited application range and a safety threat of lead ion leakage.
The perovskite in situ growth scheme based on lead ion rivet strategy is adopted to fix lead ions through ion bonding, inhibit their migration, and use ion coordination to achieve controllable growth of perovskite nanocrystals, combined with wet spinning technology Prepare perovskite fluorescent quantum dot continuous long fibers.
Improve the stability and safety of perovskite quantum dots, avoid the risk of lead leakage, achieve high fluorescence emission intensity in water and polar solvents, simplify the preparation process, reduce costs, and is suitable for flexible electronic display devices .
Smart Images

Figure CN119121428A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fiber manufacturing technology, in particular to a method for preparing continuous long fibers of perovskite fluorescent quantum dots. Background Art
[0002] With the rapid development of information technology, the demand for flexible display of electronic products is becoming stronger and stronger, and smart wearable flexible electronic display technology occupies an increasingly important position in the national economy. Perovskite quantum dots (PQDs) are a type of promising optoelectronic display materials developed in recent years. They have many advantages such as high brightness range, wide color gamut, long-range charge carrier diffusion, narrow luminescence half-width (FWHM≈20nm), high defect tolerance, tunable band gap, and easy synthesis. They have attracted extensive attention from domestic manufacturers and scientific researchers, and have shown extraordinary application potential in many fields such as solar thin-film batteries, luminescent fibers, multiphoton imaging, photoelectric detection, and photocatalysis. The new generation of perovskite quantum dot display technology, with its excellent optoelectronic performance and rich accumulation of independent intellectual property rights, is of great significance to promoting the localization process of flexible electronic display devices, and is also an important way for my country to achieve technological leadership in the field of flexible electronic optical displays.
[0003] At present, the bottleneck problem of perovskite quantum dot technology is mainly reflected in the lack of stability, which makes quantum dot materials subject to strict conditions in the device construction process. Due to the intrinsic ionic salt characteristics of perovskite quantum dots, PQDs are extremely sensitive to external environmental conditions (such as humidity, temperature, polar solvents, light, oxygen), and are easily affected by the environment, resulting in surface damage, phase change and abnormal grain growth. Especially when exposed to water and polar solvent systems, PQDs will quickly lose structural integrity and optical properties within a few seconds, resulting in fluorescence quenching, which seriously limits the practical application and development of perovskite quantum dot materials. Quantum dot materials cannot involve water or any other polar solvents, which not only greatly increases the production cost, but also seriously restricts its scope of application. Therefore, the preparation method of perovskite fluorescent fibers is very limited, and is limited to a few specific scenarios such as electrospinning and air-jet spinning that do not involve special solvents. The production conditions are relatively harsh, and continuous long fibers cannot be prepared. In addition, when encountering polar molecules, it is easy to dissociate and release lead ions (heavy metal human environmental toxins), resulting in potential biological toxicity threats, which seriously restricts its practical application. Therefore, how to improve the stability and safety of lead halide perovskite quantum dots under complex environmental conditions has always been a hot topic in scientific research.
[0004] Atomic layer deposition (ALD) is an effective method to solve the stability problem of perovskite quantum dots. 2 、Al 2 O 3 、TiO2 The invention discloses a method for synthesizing perovskite nanoparticles with dual protection of pore confinement-shell isolation, which realizes the nanoscale coating of perovskite quantum dots by atomic layer deposition technology, effectively isolates the influence of the environment on perovskite quantum dots, and has good dispersibility even in highly polar solvents such as water and ethanol, greatly improving the stability and practical application range of perovskite quantum dots. However, the applicant found in the study that surface compatibility has a key influence on the density of the ALD shell. The surface of the perovskite quantum dots synthesized by the traditional method is rich in a large number of organic ligands, which gather on the surface of the perovskite quantum dots and easily form steric hindrance between the substrate and the grains, preventing the adsorption and deposition of ALD precursor molecules, resulting in a large number of cracks and holes in the ALD shell during the growth process, which seriously reduces the density. In addition, the existing coating technology is not perfect. It is difficult to completely isolate the perovskite crystal from the external environment without being affected, especially in a high temperature and high humidity environment for a long time (such as sweat immersion during exercise). The encapsulation layer is still susceptible to penetration or damage by the external environment. Once the water in the environment comes into contact with the perovskite nanocrystals, the perovskite will quickly dissociate and release Pb 2+ Entering the water body, causing a greater risk of lead leakage. This is unacceptable for wearable devices. Therefore, developing a new ligand-free growth strategy for perovskite quantum dots and finding a better way to solve lead ion leakage are of great significance to the development of quantum dot technology. Summary of the invention
[0005] In view of the shortcomings of the above-mentioned prior art, the present invention proposes a perovskite in-situ growth scheme based on the lead ion rivet strategy, which inhibits the migration of lead ions through ionic bonding, and then uses ion coordination to achieve the controllable growth of perovskite nanocrystals under the condition of lead ion constraint. The innovative idea of this scheme is to introduce the lead capture process from the early stage of perovskite crystal growth. Each lead is strictly fixed on the surface of the matrix material, fundamentally controlling the movement and migration of lead. Even if the perovskite dissociates, it will not release free Pb into the environment. 2+, thereby reducing the risk of lead leakage of perovskite materials. In addition, due to the riveting effect of lead ions, the abnormal growth of perovskite grains is suppressed, and the ligand-free growth scheme of perovskite grains is realized, which is more conducive to the deposition of ALD precursors. The present invention introduces the lead rivet strategy into the system to prepare perovskite nanoparticles, and synthesizes fluorescent fibers by wet spinning. The present invention provides a method for preparing continuous long fibers of perovskite fluorescent quantum dots, avoiding the technical problem that the density of the atomic layer deposition shell layer in the prior art cannot meet the use requirements; avoiding the problem that the stability of perovskite quantum dots is insufficient, water and any other polar solvents cannot be involved, the production cost is high, and the application scope is seriously restricted; avoiding the limitations of the preparation method of perovskite fluorescent quantum dot fibers, there are only a few specific preparation scenarios that do not involve special solvents; avoiding the problem that the production conditions of perovskite fluorescent quantum dot fibers are relatively harsh and continuous long fibers cannot be prepared. The safety problem of lead leakage that may occur in the wearing process of perovskite fluorescent quantum dot fibers is avoided.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing continuous long fibers of perovskite fluorescent quantum dots, comprising the following steps:
[0007] (1) Preparation of perovskite quantum dot nanoparticles using the B-site cation (lead) adsorption strategy;
[0008] (2) dissolving TPU in DMF to prepare a TPU solution, dissolving the nanoparticles prepared in step (1) in the TPU solution, and heating and stirring to prepare a spinning solution;
[0009] (3) Using wet spinning technology, the spinning solution is added to the spinneret, the spinneret is placed in a coagulation bath for coagulation, and finally the continuous long fibers are collected by a drawing device.
[0010] Furthermore, the B-site cation adsorption strategy in step (1) comprises the following steps:
[0011] S1, preparing mesoporous nanoparticles as a base material, wherein the base material is one or more of an inorganic material and a metal material; S2, performing a thiol treatment on the base material;
[0012] S3, mixing the precursor solution containing the B-site cation with the thiol-modified base material, and using the strong adsorption of the thiol group to tightly attach the B-site cation to the surface of the base material to obtain a B-site cation structure;
[0013] S4, mixing a precursor solution containing A-site cations with the product of step 3, and then causing the A-site cations to coordinate with the B-site cations, thereby achieving coordinated growth of perovskite quantum dots on the surface of the substrate material;
[0014] S5. Perform inert shell coating using an atomic layer deposition system, wherein the oxide inert shell is one or more of a silicon dioxide shell, an aluminum oxide shell, and a titanium dioxide shell.
[0015] Furthermore, the preparation steps of S1 include: using tetraethoxysilane as a silicon source, ethanol as a solvent, ammonia water to adjust the pH, CTAB as a template material, n-hexane to adjust the mesopore size, and hydrochloric acid solution to remove the template material. A spherical base material with a diameter of 50 to 150 nm is synthesized at a certain temperature.
[0016] Further, the preparation steps of S2 include:
[0017] S2.1, adding 3-mercaptopropyltrimethoxysilane as a raw material into anhydrous ethanol to prepare a mercapto solution;
[0018] S2.2, mixing the thiol solution with the base material in step 1, and reacting for 6-12 hours with water as solvent;
[0019] S2.3. Wash with anhydrous ethanol for 3-5 times and dry to obtain a thiol-containing base material.
[0020] 5. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 4, characterized in that: the preparation step S3 comprises: firstly mixing a certain concentration of BX 2 The precursor of the B-site cation is obtained by dissolving it in dimethylformamide, wherein the B element is one or more of the Pb element, the Sn element, and the Mn element; and the X element is a halogen element; and then the precursor is fully mixed with the thiol-modified base material, and after a period of reaction, the precursor is centrifuged and washed to obtain the base material adsorbed with the B-site cation.
[0021] Further, the preparation step of S4 comprises:
[0022] S4.1. dissolving a certain concentration of AX in dimethylformamide to obtain an A-site cation precursor, wherein the A element is one or more of Cs element, MA element, and FA element; and the X element is a halogen element;
[0023] S4.2, fully mixing with the base material adsorbed with the B-site cation in step 3;
[0024] S4.3. After a period of reaction, remove the excess solution by suction and dry or place it in a poor solvent to achieve the coordinated growth of perovskite quantum dots.
[0025] Further, the preparation step of S5 comprises:
[0026] S5.1, dispersing the product powder prepared in step 4 in the reaction chamber;
[0027] S5.2, placing in an atomic layer deposition system preheated to 50-200°C;
[0028] S5.3. Alternately introduce aluminum source pulses and water source pulses, and then introduce inert gas for flushing after the aluminum source pulses and the water source pulses, wherein the source bottle temperature setting range is 10-35°C, the aluminum source pulse time is 0.1-0.5s, the inert gas purge time is 5-20s, the water source pulse time is 0.1-0.5s, the inert gas purge time is 5-20s, the cycle number is 10-200, and the inert gas is one or more of nitrogen, argon, and helium.
[0029] Furthermore, in the step (2), TPU is dissolved in DMF at a mass ratio of 10%-30%, heated to dissolve at 60°C for 1 hour, and then stirred in a magnetic stirrer for 4-8 hours to form a TPU solution, 5%-10% nanoparticles are added to the TPU solution, stirred at room temperature for 20-30 minutes, and finally vacuumed in a vacuum oven at room temperature for 2 hours to remove bubbles in the spinning solution to form a spinning solution.
[0030] Furthermore, in step (3), the spinneret includes a 5 ml needle tube, a 19G dispensing needle, a transparent silicone tube, and a plastic Luer connector. The propulsion speed of the spinneret is 6 mm / min, and the propulsion time is 5 min. After the spinning solution enters the coagulation bath, it is quickly formed and the fineness changes under the stretching action of the stretching device. The continuous long fibers are collected and finally dried at room temperature for 2 days to obtain continuous long fibers of perovskite fluorescent quantum dots.
[0031] Furthermore, the coagulation bath is deionized water.
[0032] The beneficial effects of the preparation method of the perovskite fluorescent quantum dot continuous long fiber of the present invention are: an innovative perovskite quantum dot coordination synthesis technology based on the B-site ion adsorption strategy is proposed, which not only solves the problem of the influence of the steric effect of the ligand molecule on the ALD shell density, but also avoids the biosafety problem that may be caused by the desorption of the B-site ions; no additional ligand molecules are required, and it is applicable to the surface of various substrate materials, which is a universal general-purpose synthesis scheme; the perovskite nanoparticles prepared by the B-site ion adsorption strategy have excellent stability and can maintain high fluorescence emission intensity for a long time in strong polar solvents such as water and ethanol; the perovskite fluorescent quantum dot continuous long fiber is prepared by innovative wet spinning technology, and the preparation method is simple to operate, low cost, and can be realized on a large scale Batch preparation: TPU and DMF are mixed, heated and stirred to form a TPU solution, and then perovskite nanoparticles are added to dissolve the perovskite nanoparticles in the TPU solution. After solidification in a solidification bath, most of the perovskite nanoparticles are wrapped in the formed long fibers, isolating them from contact with water and any other polar solvents, thereby ensuring the stability of the perovskite nanoparticles. At the same time, the perovskite nanoparticles on the surface of the long fibers also have excellent stability due to the B-site ion adsorption strategy. The perovskite fluorescent quantum dot continuous long fibers prepared in this way have good stability, high fluorescent brightness, and pure chromaticity, and can be widely used in flexible electronic display devices. The diameter of the long fibers and the content of the perovskite fluorescent quantum dots in the long fibers can be adjusted as needed to meet the needs of various flexible electronic display devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 Schematic diagram of the experimental steps of the present invention for in-situ growth of perovskite nanocrystals by using the B-site cation adsorption strategy and preparing stable perovskite nanoparticles by atomic layer deposition (ALD);
[0034] Figure 2 This is a schematic diagram of the experimental steps from preparing perovskite nanoparticles to preparing TPU fluorescent fibers using the B-site cation adsorption strategy adopted in the present invention;
[0035] Figure 3 This is a transmission electron microscope micrograph of perovskite quantum dot nanoparticles prepared by the B-site cation adsorption strategy of the present invention;
[0036] Figure 4 The second high-resolution transmission electron microscope micrograph of the perovskite nanoparticles prepared by the B-site cation adsorption strategy of the present invention;
[0037] Figure 5 X-ray diffraction patterns of perovskite quantum dot nanoparticles before and after ALD coating with aluminum oxide;
[0038] Figure 6The fluorescence spectrum of the sample in step S5 is obtained by measuring the absorption spectrum, emission spectrum and half-maximum full width by a fluorescence spectrometer;
[0039] Figure 7 The actual photos of the sample in step s5 under sunlight and ultraviolet light respectively;
[0040] Figure 8 The fluorescence lifetime curve of the sample in step s5 measured by a fluorescence spectrometer;
[0041] Fig. 9 Spectra of samples with different emission wavelengths obtained using different halogen ratios in step S4.1;
[0042] Fig.10 The stability diagram of perovskite nanoparticles in water after being coated with an inert oxide shell;
[0043] Fig.11 It is a schematic diagram of the spinning device principle;
[0044] Fig.12 This is a real picture of the continuous long fiber of perovskite fluorescent quantum dots under sunlight and ultraviolet light;
[0045] Fig.13 This is a scanning electron microscope image of continuous long fibers of perovskite fluorescent quantum dots;
[0046] Fig.14 The stress-strain diagram of pure TPU and wet-spun fiber doped with 10% perovskite nanoparticles. The change in fiber strength before and after doping with perovskite nanoparticles was measured by a universal tensile machine. It was found that the elongation at break of the fiber after doping with particles was 364.72%, which was lower than 468.14% of pure TPU fiber. This is because the addition of perovskite nanoparticles will form steric hindrance, occupy the connection space of TPU polymer, and reduce the connection points between TPU molecules. In addition, the nanoparticles in the fiber will also make the fiber more prone to stress concentration in a local area, thereby causing the fiber to break. However, the reduction in breaking strength is also related to the doping amount. Under the premise of ensuring the fluorescence intensity, a slight reduction in breaking strength is acceptable.
[0047] Fig.15 Pb before and after ALD coating of mesoporous nanomaterials and after wet spinning 2+ The leakage of lead ions in the fibers before and after nanoparticle coating and after spinning was tested by inductively coupled plasma atomic emission spectroscopy (ICP). 2+The leakage problem has been well solved, effectively reducing the potential toxic threat of lead ions and heavy metal ions to life systems. After 5 days of continuous immersion, the lead ion concentration in the perovskite fluorescent fiber aqueous solution was only 1.58 ppb, which is almost negligible. DETAILED DESCRIPTION
[0048] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments:
[0049] Example 1
[0050] like Figure 1-15 As shown, a method for preparing a continuous long fiber of perovskite fluorescent quantum dots comprises the following steps:
[0051] (1) Preparation of perovskite quantum dot nanoparticles using the B-site cation adsorption strategy;
[0052] S1. Preparation of mesoporous silica (mSiO 2 ) nanoparticles as substrate. Specifically, tetraethoxysilane (TEOS) is used as silicon source, ethanol is used as solvent, ammonia water is used to adjust pH, CTAB is used as template material, n-hexane is used to adjust mesopore size, and hydrochloric acid solution is used to remove template material. Spherical substrate materials with a diameter of 50-150nm are synthesized at a certain temperature. Generally: 0.5g CTAB is dissolved in 80ml ultrapure water, 1ml ammonia water is added, and a 35°C water bath is formed to form a clear solution. Then 6ml is mixed with 2.5ml TEOS and slowly dripped into the clear solution, reacted at 35°C for 12h, and after the reaction, ultrapure water and alcohol are alternately washed 2-3 times, centrifuged to obtain silicon ball precipitation, and the precipitation is dispersed in 1M HCl and 100ml ethanol solution, and the water bath is 80°C for 8h. Then the alcohol and water are alternately washed once, and this step is repeated six times. Finally, mesoporous silicon ball nanoparticles are obtained by drying.
[0053] S2. The silica nanoparticles are thiolated, and other groups on the original silica are replaced by thiol-SH. Generally, 45 μl of MPTMS (3-mercaptopropyltrimethoxysilane) is added as a raw material to 15 ml of anhydrous ethanol to prepare a thiol solution, and the thiol solution is mixed with 15 ml of silica balls in step 1, and reacted for 6-12 hours with 120 ml of water as a solvent. Then, the thiol-modified silica nanoparticles are washed 3-5 times with anhydrous ethanol and dried to obtain thiolated silica nanoparticles.
[0054] S3, mixing the precursor solution containing the B-site cation with the thiol-modified substrate material, and using the strong adsorption of the thiol group to tightly attach the B-site cation to the surface of the substrate material to obtain a monolayer or sub-monolayer B-site cation structure. Specifically, 0.55 g PbBr 2Dissolve in 50 ml dimethylformamide (DMF) to obtain the B-site cation precursor, then take 7.5 ml PbBr 2 The solution was fully mixed with the mercapto-silica particles in step 2, stirred in a water bath at 55 degrees for 25 minutes, and then centrifuged and washed to obtain Pb ion-adsorbed silica nanospheres.
[0055] S4, mixing a certain concentration of the A-site cation precursor with the above particles, and then using a coprecipitation method or a solvent evaporation method, the A-site cation and the B-site cation are coordinated to react, thereby achieving the coordinated growth of perovskite quantum dots on the surface of the substrate material. Specifically, a certain concentration of 0.33g CsBr is dissolved in 50ml dimethylformamide (DMF) to obtain the A-site cation precursor, and then 4.8ml of the CsBr solution is taken and fully mixed with the silica particles adsorbed by the B-site cation in step 3, and after ultrasonic reaction for ten minutes, vacuum drying at 120°C is performed to achieve the coordinated growth of perovskite quantum dots, such as Fig. 9 As shown, it can be found that the wavelength of fluorescence emitted by the nanoparticles can be controlled by adjusting the ratio of halogens, thereby achieving spectral adjustment from blue visible light to red visible light.
[0056] S5. Use an atomic layer deposition system to coat the inert shell to improve the stability of the perovskite nanoparticles. Specifically, the perovskite nanoparticle powder prepared in step S4 is dispersed in a reaction chamber, and then placed in an atomic layer deposition system preheated to 100°C, and aluminum source pulses and water source pulses are alternately introduced. After the aluminum source pulses and water source pulses, inert gas is introduced for flushing. The source bottle temperature is set to 10-35°C, the aluminum source pulse time is 0.1-0.5s, the inert gas purge is 5-20s, the water source pulse time is 0.1-0.5s, the inert gas purge is 5-20s, and the number of cycles is 10-200. The obtained particles are photographed by high-resolution transmission electron microscopy to obtain Figure 3 , Figure 4 ,like Figure 4 As shown, the transmission electron microscope image shows the state of the perovskite material after growth and coating. The core-shell structure shows that the ALD coating has been completed and the coating is relatively uniform. The black dots in the mesopores are perovskite quantum dot crystals. Through high-resolution transmission electron microscopy, it can be seen that the lattice gap is The existence of perovskite quantum dots is proved, indicating that it is feasible to use this scheme to coordinate and grow perovskite quantum dots. Figure 5 ,like Figure 5 As shown, among which, mSiO 2 -S-CsPbBr 3It is the perovskite nanoparticle prepared in step S4. The X-ray diffraction spectrum shows that the nanoparticles prepared in step S4 have the diffraction peak of the perovskite crystal, which is consistent with the position marked on the crystal plane of card PDF18-0364, proving the integrity of the perovskite quantum dot crystal structure. The X-ray diffraction spectrum provides evidence for the authenticity and correctness of the crystal structure of the nanoparticles synthesized in each step.
[0057] Inert gas has two functions: one is to serve as a carrier gas for ALD precursors, helping the precursor source to better adhere to the substrate surface. The other function is to purge and clean. In each small cycle, the excess gas in the reaction chamber must be removed to ensure that the oxidation reaction only occurs on the surface of the substrate material. The oxide inert shell layer can be selected from one of the following: silicon dioxide shell layer, aluminum oxide shell layer, titanium dioxide shell layer, etc. The silicon dioxide shell layer can use a precursor such as tridimethylaminosilane (TDMAS, silicon source). The aluminum oxide shell layer can use a precursor such as trimethylaluminum (TMA, aluminum source). The titanium dioxide shell layer can use a precursor such as titanium tetrachloride (TiCl 4 , titanium source), etc. The water source can also be replaced by ozone as an oxidation source.
[0058] ALD can choose to deposit multiple shell layers, and the precursors corresponding to each shell layer are different. 2 O 3 , then the corresponding precursor source is TMA, which provides the Al element (similarly SiO 2 The corresponding precursor source is TDMAS). Water or ozone is an oxidant that reacts with TMA to generate Al 2 O 3 Shell.
[0059] ALD is a typical surface reaction process based on Al 2 O 3 For example, first place the substrate material in the reaction chamber and repeatedly purge it with inert gas to ensure the cleanliness of the chamber and the surface of the substrate material. Then introduce the TMA precursor. After the precursor is adsorbed on the surface of the substrate material, introduce inert gas to purge and remove the excess precursor in the chamber, leaving only the part adsorbed on the surface of the substrate material. Then introduce water or ozone to oxidize TMA to generate Al 2 O 3 Because TMA is only adsorbed on the surface of the substrate in a thin layer, the Al 2 O 3 This is called a circle, and the Al deposited in each circle is 2 O 3The shell is only about 0.1nm thick. Therefore, in order to obtain a higher shell thickness, the above process needs to be repeated. For example, if the cycle is repeated 100 times, then about 10nm of Al can be obtained. 2 O 3 The shell.
[0060] Fluorescence spectroscopy analysis of perovskite quantum dot nanoparticles
[0061] 0.1 g of the perovskite nanoparticles prepared in step (1) was placed in a 5 ml centrifuge tube, 3 ml of water was added for ultrasonic dispersion, and then transferred to a quartz cuvette using a pipette, and photoluminescence data was collected using a fluorescence spectrometer. Figure 6 It can be seen that under the excitation of 365nm light source, the perovskite nanoparticles coated with the oxide inert shell can emit stable fluorescence, with the emission peak at 517nm and the half-peak width of 23nm. The fluorescence intensity is high, the emission spectrum is narrow, and the color purity is high.
[0062] The CsBr and PbBr used 2 By replacing the corresponding CsX, PbX2 as precursors, where X is Cl, Br, I halogen elements, and repeating the operation, perovskite nanoparticles of different compositions can be obtained. Figure 7 As shown, from left to right are CsPbBrCl 2 、CsPbBr 3 and CsPbI 3 Digital photo of perovskite nanoparticles of the components dispersed in aqueous solution, with an excitation light source of 365nm. 2 Blue, CsPbBr 3 Green, CsPbI 3 Is red.
[0063] Perovskite quantum dot nanoparticle stability test
[0064] After the perovskite nanoparticles coated with the oxide inert shell were stored in a toluene-water two-phase interface solution for 3 days, the sample photos were taken under fluorescent light and ultraviolet light (365nm) respectively. It can be clearly seen from the figure that the perovskite nanoparticles coated with the inert shell are more inclined to disperse in the water phase, showing good hydrophilic properties. At the same time, they show obvious bright green fluorescence under ultraviolet light excitation, proving that the perovskite nanoparticles prepared by this scheme have excellent hydrophilicity and stability.
[0065] Fig. 9The figure shows the dynamic fluorescence spectrum data of perovskite nanoparticles coated with an oxide inert shell layer in water after continuous stirring for 200 minutes. The figure shows the stability comparison of perovskite nanoparticles in water after four different numbers of inert shell deposition (50, 100, 150, and 200). It can be clearly seen from the figure that with the increase in the number of shell deposition circles, the stability of perovskite nanoparticles in water is significantly improved (perovskite nanoparticles that are not coated with a shell layer will quench fluorescence the moment they come into contact with water). When the number of deposition circles reaches 200, the fluorescence intensity of perovskite nanoparticles in water is almost not weakened, indicating that this technology can significantly improve the stability of perovskite quantum dot materials.
[0066] Fig.10 The luminescence of perovskite nanoparticles coated with an oxide inert shell after being dispersed in water for 90 days shows that the ions coated with 200 circles still have strong fluorescence brightness after 90 days in water. Compared with the prior art, the product of this application has good surface compatibility and meets the requirements of ALD dense shell coating, which can significantly improve the stability of perovskite quantum dots, such as Fig.10 As shown in the figure, the thickness of each aluminum oxide coating by ALD is about 0.1nm. The perovskite nanoparticles coated with different numbers of aluminum oxide were immersed and stirred in water continuously, and the fluorescence spectrum intensity was measured every 10 minutes. From the figure, it can be found that with the increase of aluminum oxide coating thickness, the stability of the particles gradually increases. At 200 circles, it can almost achieve complete resistance to water.
[0067] Step (2), dissolving TPU in DMF at a mass ratio of 10%-30%, heating to 60°C for 1 hour, stirring in a magnetic stirrer for 4-8 hours to form a TPU solution, adding 5%-10% nanoparticles to the TPU solution, stirring at room temperature for 20-30 minutes, and finally evacuating the solution in a vacuum oven at room temperature for 2 hours to remove bubbles in the spinning solution to form a spinning solution. Step (3), injecting the spinning solution into a spinning device, such as Fig.11 As shown, the propulsion speed of the spinneret is 6 mm / min, and the propulsion time is 5 min. After the spinning solution enters the coagulation bath, it is quickly formed and the fineness changes under the stretching action of the stretching device. The continuous long fibers are collected and finally dried at room temperature for 2 days to obtain the continuous long fibers of perovskite fluorescent quantum dots, as shown in FIG. Fig.13 As shown, it can be seen through electron microscopy that perovskite nanoparticles can be evenly dispersed in wet-spun fibers as fluorescent materials.
[0068] Fluorescence spectroscopy test was performed on the prepared perovskite fluorescent quantum dot continuous long fibers.
[0069] Under 365nm ultraviolet excitation light, the fluorescent fiber has bright emission at 517nm, and has a full width at half maximum (FWHM) of 23nm, pure color, and greatly retains the characteristics of the particles, all thanks to the good stability of the perovskite quantum dot nanoparticles. Neither the organic solvent DMF nor deionized water can destroy the structure of the particles.
[0070] The ICP lead ion concentration test was carried out on the prepared perovskite fluorescent quantum dot continuous long fibers.
[0071] All fibers spun from the spinning solution prepared in step (2) and 0.1% perovskite quantum dot nanoparticles were immersed in 1L of water, and samples were taken every five days to test the Pb content in the water. 2 + concentration (such as Fig.15 As shown): After wet spinning, the Pb content in the sample 2 + The concentration decreases rapidly. This is because the dual protection effect of the stable perovskite quantum dot nanoparticles and the polymer TPU greatly reduces the Pb in the fiber. 2+ Potential toxic threats to organisms and the environment.
[0072] The prepared perovskite fluorescent quantum dot continuous long fibers were subjected to stability tests.
[0073] A 5 cm long continuous fiber of perovskite fluorescent quantum dots was placed in a four-transparent cuvette and immersed in 3 ml of deionized water solution. The fluorescence intensity was tested and recorded every day. The experimental results showed that the fluorescence intensity of the wet-spun fiber had almost no significant change in 13 days. Therefore, we believe that the wet-spun fiber has good stability.
[0074] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.
Claims
1. A method for preparing continuous long fibers of perovskite fluorescent quantum dots, characterized in that: The following steps are involved: (1) Preparation of perovskite quantum dot nanoparticles using the B-site cation adsorption strategy; (2) dissolving TPU in DMF to prepare a TPU solution, dissolving the nanoparticles prepared in step (1) in the TPU solution, and heating and stirring to prepare a spinning solution; (3) Using wet spinning technology, the spinning solution is added to the spinneret, the spinneret is placed in a coagulation bath for coagulation, and finally the continuous long fibers are collected by a drawing device.
2. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 1, characterized in that: The B-site cation adsorption strategy in step (1) comprises the following steps: S1. Prepare nanoparticles as a base material, wherein the base material is one or more of an inorganic material and a metal material; S2, performing thiol treatment on the base material; S3, mixing the precursor solution containing the B-site cation with the thiol-modified base material, and using the strong adsorption of the thiol group to tightly attach the B-site cation to the surface of the base material to obtain a B-site cation structure; S4, mixing a precursor solution containing A-site cations with the product of step 3, and then causing the A-site cations to coordinate with the B-site cations, thereby achieving coordinated growth of perovskite quantum dots on the surface of the substrate material; S5. Perform inert shell coating using an atomic layer deposition system, wherein the oxide inert shell is one or more of a silicon dioxide shell, an aluminum oxide shell, and a titanium dioxide shell.
3. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 2, characterized in that: The preparation steps of S1 include: using tetraethoxysilane as a silicon source, ethanol as a solvent, ammonia water to adjust the pH, CTAB as a template material, n-hexane to adjust the mesopore size, and hydrochloric acid solution to remove the template material. A spherical base material with a diameter of 50 to 150 nm is synthesized at a certain temperature.
4. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 3, characterized in that: The preparation steps of S2 include: S2.1, adding 3-mercaptopropyltrimethoxysilane as a raw material into anhydrous ethanol to prepare a mercapto solution; S2.2, mixing the thiol solution with the base material in step 1, and reacting for 6-12 hours with water as solvent; S2.
3. Wash with anhydrous ethanol for 3-5 times and dry to obtain a thiol-modified base material.
5. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 4, characterized in that: The preparation steps of S3 include: first dissolving a certain concentration of BX2 in dimethylformamide to obtain a B-site cation precursor, wherein the B element is one or more of the Pb element, the Sn element, and the Mn element; the X element is a halogen element; and then fully mixing with the thiol-modified base material, centrifuging and washing after a period of reaction to obtain a base material with B-site cation adsorbed.
6. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 5, characterized in that: The preparation steps of S4 include: S4.
1. dissolving a certain concentration of AX in dimethylformamide to obtain an A-site cation precursor, wherein the A element is one or more of Cs element, MA element, and FA element; and the X element is a halogen element; S4.2, fully mixing with the base material adsorbed with the B-site cation in step 3; S4.
3. After a period of reaction, vacuum dry or place in a poor solvent to achieve the coordination growth of perovskite quantum dots.
7. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 6, characterized in that: The preparation steps of S5 include: S5.1, dispersing the product powder prepared in step 4 in the reaction chamber; S5.2, placing in an atomic layer deposition system preheated to 50-200°C; S5.
3. Alternately introduce aluminum source pulses and water source pulses, and then introduce inert gas for flushing after the aluminum source pulses and the water source pulses, wherein the source bottle temperature setting range is 10-35°C, the aluminum source pulse time is 0.1-0.5s, the inert gas purge time is 5-20s, the water source pulse time is 0.1-0.5s, the inert gas purge time is 5-20s, the cycle number is 10-200, and the inert gas is one or more of nitrogen, argon, and helium.
8. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 7, characterized in that: In the step (2), TPU is dissolved in DMF at a mass ratio of 10%-30%, heated to dissolve at 60°C for 1 hour, and then stirred in a magnetic stirrer for 4-8 hours to form a TPU solution, 5%-10% nanoparticles are added to the TPU solution, stirred at room temperature for 20-30 minutes, and finally vacuumed in a vacuum oven at room temperature and allowed to stand for 2 hours to remove bubbles in the spinning solution to form a spinning solution.
9. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 8, characterized in that: In step (3), the spinneret includes a 5 ml needle tube, a 19G dispensing needle, a transparent silicone tube, and a plastic Luer connector. The propulsion speed of the spinneret is 6 mm / min, and the propulsion time is 5 min. After the spinning solution enters the coagulation bath, it is quickly formed and the fineness changes under the stretching action of the stretching device. The continuous long fibers are collected and finally dried at room temperature for 2 days to obtain continuous long fibers of perovskite fluorescent quantum dots.
10. The method for preparing a continuous long fiber of perovskite fluorescent quantum dots according to claim 9, characterized in that: The coagulation bath is deionized water.
Citation Information
Patent Citations
Preparation method of perovskite nanoparticles with dual protection of pore confinement and shell isolation
CN110205110B
